POTENSI KEHILANGAN HASIL PANEN DAN PASCA PANEN JAGUNG DI KABUPATEN LAMPUNG SELATAN - Valeriana Darwis (Journal of Food System & Agribusiness, 2018)
Poor harvest and post harvest handling can reduce corn production in terms of quantity and quality. Therefore, this paper aims to know the potential loss of maize crops and post-harvest through the habits of farming cultivation in South Lampung, especially during the activities of harvesting, shelling, drying and storing. The results of the study showed that corn farmers understand the importance of harvest and post harvest handling in producing quality corn production. However, not all farmers put their understanding into practice even if the technology for harvesting and post-harvest activities have been invented and implemented by the ministry of agriculture. In order to increase the income of corn farmers, the socialization and demonstration of the use of the tools or technology specific to harvest and post harvest location needs to be enhanced.Keywords: loss, harvest, post harvest and corn